Comparison of Resting Full-Cycle Ratio and Fractional Flow Reserve in a German Real-World Cohort - Wienemann, Hendrik; Meyer, Annika; Mauri, Victor; Baar, Till; Adam, Matti; Baldus, Stephan; Halbach, Marcel (Frontiers in Cardiovascular Medicine, 2021)
The aim of this study was to evaluate non-hyperemic resting pressure ratios (NHPRs), especially the novel "resting full-cycle ratio" (RFR; lowest pressure distal to the stenosis / aortic pressure during the entire cardiac cycle), compared to the gold standard fractional flow reserve (FFR) in a “real-world” setting. The study included patients undergoing coronary pressure wire studies at one German University Hospital. No patients were excluded based on any baseline or procedural characteristics, except for insufficient quality of traces. The diagnostic performance of four NHPRs vs. FFR ≤0.80 was tested. Morphological characteristics of stenoses were analyzed by quantitative coronary angiography. 617 patients with 712 coronary lesions were included. RFR showed a significant correlation with FFR (r =0.766, p<0.01). Diagnostic accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of RFR were 78% (95% confidence interval = 75; 81), 72% (65; 77), 81% (77; 84), 63% (58; 67), and 86% (84; 89). Relevant predictors for discordance of RFR ≤0.89/FFR >0.8 were LAD lesions, peripheral artery disease, age and female sex. Predictors for discordance of RFR >0.89/FFR ≤0.8 included non-RCX lesions, percent diameter stenosis and previous percutaneous coronary intervention in the target vessel. RFR and all other NHPRs were highly correlated with each other. All NHPRs have a similar correlation with the gold standard FFR and may facilitate the acceptance and implementation of physiological assessments of lesion severity. However, we found approximately 20% discordant results between NHPRs and FFR in our “all-comers” German cohort.